Foreign direct invistment in developing Asia trends, effects, and likely issues for the forthcoming WTO negotions, April 2003 Douglas H. Brooks, Emma Xiaoqin Fan, Leo R. Sumulong - BROOKS, Douglas H; Sumulong, Lea R; Xiaoqin Fan, Emma (Asian Development Bank, 2003)
i, 44 hlm ilus 28 cm